Voltammetric Determination of Sulfonamides with a Modified Glassy Carbon Electrode Using Carboxyl Multiwalled Carbon Nanotubes - He,Bao-shan (2016)
New glassy carbon electrode (GCE) modified with carboxyl multiwalled carbon nanotubes (MWCNTs) and treated with ultrasonic dispersing in N,N-dimethylfomamide (DMF) media, namely DMF/carboxyl/MWCNTs/GCE, was prepared for electrochemical determination of sulfonamides (SAs). Electrochemical behavior of SAs based on DMF/carboxyl/MWCNTs/GCE was investigated by cyclic voltammetry and impedance spectroscopy. The effects of various experimental parameters on the response of electrode such as pH of buffer, scan rate and the amount of modification were optimized. Under the optimal conditions, the obtained sensor presented linear response to SAs in the range of 5.0 × 10-7 to 1.1 × 10-4 mol L-1 of sulfonamide (R = 0.999), sulfamethazine (R = 0.990), sulfadiazine (R = 0.997), sulfamethoxazole (R = 0.996) and the limits of detection of 1.65 × 10-8, 3.19 × 10-8, 6.76 × 10-8 and 9.41 × 10-8 mol L-1, respectively. The recoveries were in the range of ca. 85-103% with relative standard deviation (RSD) < 5%. The sensor was tested by cyclic voltammetry with repeatability and stability of more than 90% of its original activity. The proposed method might offer feasibility and applicability of the sensor for further complex sulfonamides compounds.